Comprehensive Analysis of the Butyrate-Metabolism-Related Gene Signature in Tumor Microenvironment-Infiltrating Immune Cells in Clear Cell Renal Cell Carcinoma - Tang, Gang; Guan, Haochen; Du, Zhiyong; Yuan, Weijie (Frontiers in Cell and Developmental Biology, 2022)
A wealth of experimental evidence has validated that butyrate is capable of inhibiting tumorigenesis, while the potential role of butyrate metabolism in the tumor immune microenvironment (TIME) has been rarely explored. This study aims to explore the potential of butyrate-metabolism-related genes as prognostic biomarkers and their correlations with immune infiltrates in clear cell renal cell carcinoma (ccRCC) patients. Based on The Cancer Genome Altas dataset (TCGA; n = 539). A total of 22 differentially expressed genes (DEGs) related with butyrate metabolism in ccRCC and normal samples. Among them, a prognostic signature involving 6 butyrate-metabolism-related genes was created (Bu-Meta-GPS) in the training set (n = 271) and validation set (n = 268), and risk scores were calculated based on them. ccRCC patients with high-risk scores exhibited unfavorable prognosis, high immunoscore, upregulated immuno-oncological targets (PD1, PD-L1, CTLA4 and CD19) and distinct immune-cell infiltration than those with low-risk scores. High-risk ccRCC patients without radiotherapy had a better survival than radiotherapy-treated patients. The negative regulation of cytokine production and cytokine-mediated signaling pathways were remarkably enriched in ccRCC patients with high-risk scores. A nomogram was then formulated to assess the overall survival (OS) of ccRCC. In summary, we illuminated the key role of butyrate metabolism in ccRCC TIME. The developed Bu-Meta-GPS was a sensitive predictive biomarker for the prognosis of ccRCC, which also provided new perspectives in improving immunotherapeutic efficacy.